2x-6(6x-14)=-120

Simple and best practice solution for 2x-6(6x-14)=-120 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6(6x-14)=-120 equation:


Simplifying
2x + -6(6x + -14) = -120

Reorder the terms:
2x + -6(-14 + 6x) = -120
2x + (-14 * -6 + 6x * -6) = -120
2x + (84 + -36x) = -120

Reorder the terms:
84 + 2x + -36x = -120

Combine like terms: 2x + -36x = -34x
84 + -34x = -120

Solving
84 + -34x = -120

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-84' to each side of the equation.
84 + -84 + -34x = -120 + -84

Combine like terms: 84 + -84 = 0
0 + -34x = -120 + -84
-34x = -120 + -84

Combine like terms: -120 + -84 = -204
-34x = -204

Divide each side by '-34'.
x = 6

Simplifying
x = 6

See similar equations:

| h=-16t^2+16t+1200 | | 6(2x-12)=8(2x-16) | | 6x+5=-5+2x+26 | | 3a^2+xa=x^2 | | -9-x=7 | | -4x-4(x+14)=-136 | | 6(2-t)-(3-4t)=2 | | 4=4-6r-7r | | 2y=5(4)-12 | | 12x-4x=-40 | | 104-7x=20x+17 | | 3x+3(3x-15)=39 | | 13-7x=38-14x | | 8(x-9)=6(2x-12)-4x | | 45x^2+10x-0.2=0 | | x+9=-3x+11 | | x^3-5x^2+6x+2=0 | | v-15=-2 | | 5(1270)+(1270)=7620 | | ln(7x+12)-ln(x)=ln(8) | | 5(y-1)=3y+9 | | 428=2*84+40*h | | 25+75x=925 | | 5(2x-4)+6X= | | 4(6-2m)-m= | | -3x^4-3x^2+1=0 | | 10-2x=32 | | 2(6y+6)+10= | | -3(y+2)=2(y+6)+7 | | 9(r+2)-4r= | | 2(5z-5(2z-3))=4z-12 | | 0.6m+2=10 |

Equations solver categories